ANALYSIS OF MORPHOMETRIC INDICATORS OF SCARDINIUS ERYTHROPHTHALMUS AND CARASSIUS GIBELIO IN THE ISFAYRAMSAY RIVER (Scientific journal of the Fergana State University, 2024)
The article studied and analyzed the morphological, morphometric, meristic and some biological indicators of Scardinius erythrophthalmus and Carassius gibelio living in the Isfayramsay river basin in the upper reaches of the Syrdarya River. The morphometric parameters of the Carassius gibelio caught in Isfayramsay River and the upper reaches of the Syrdarya were comparatively analyzed. Based on morphometric indicators, the ratio of individual body parts to the total body length was determined. Some differences in some morphometric characteristics of Carassius gibelio individuals from the Isfayramsay River and the upper reaches of the Syrdarya River were clarified. The article also discusses the issue of the introduction of Carassius gibelio to the reservoirs of our republic, their distribution across reservoirs and the characteristics of biological indicators in different types of reservoirs.